Grade and stage misclassification in intermediate unfavorable‐risk prostate cancer radiotherapy candidates. Issue 10 (1st April 2022) - Sorce, Gabriele; Flammia, Rocco Simone; Hoeh, Benedikt; Chierigo, Francesco; Hohenhorst, Lukas; Panunzio, Andrea; Stabile, Armando; Gandaglia, Giorgio; Tian, Zhe; Tilki, Derya; Terrone, Carlo; Gallucci, Michele; et al.
Abstract: Background: We tested for upgrading (Gleason grade group [GGG] ≥ 4) and/or upstaging to non‐organ‐confined stage ([NOC] ≥ pT3/pN1) in intermediate unfavorable‐risk (IU) prostate cancer (PCa) patients treated with radical prostatectomy, since both change the considerations for dose and/or type of radiotherapy (RT) and duration of androgen deprivation therapy (ADT). Methods: We relied on Surveillance, Epidemiology, and End Results (2010–2015). Proportions of (a) upgrading, (b) upstaging, or (c) upgrading and/or upstaging were tabulated and tested in multivariable logistic regression models. Results: We identified 7269 IU PCa patients. Upgrading was recorded in 479 (6.6%) and upstaging in 2398 (33.0%), for a total of 2616 (36.0%) upgraded and/or upstaged patients, who no longer fulfilled the IU grade and stage definition. Prostate‐specific antigen, clinical stage, biopsy GGG, and percentage of positive cores, neither individually nor in multivariable logistic regression models, discriminated between upgraded and/or upstaged patients versus others. Conclusions: IU PCa patients showed very high (36%) upgrading and/or upstaging proportion. Interestingly, the overwhelming majority of those were upstaged to NOC. Conversely, very few were upgraded to GGG ≥ 4. In consequence, more than one‐third of IU PCa patients treated with RT may be exposed to suboptimal dose and/or type of RT and to insufficient duration of ADT, since their true grade and stage corresponded to high‐risk PCa definition, instead of IU PCa. Data about magnetic resonance imaging were not available but may potentially help with better stage discrimination.